Preterm Birth Affects the Risk of Developing Immune-Mediated Diseases - Goedicke-Fritz, Sybelle; Härtel, Christoph; Krasteva-Christ, Gabriela; Kopp, Matthias V.; Meyer, Sascha; Zemlin, Michael (Frontiers in Immunology, 2017)
Prematurity affects approximately 10% of all children, resulting in drastically altered antigen exposure due to premature confrontation with microbes, nutritional antigens and other environmental factors. During the last trimester of pregnancy, the fetal immune system adapts to tolerate maternal and self-antigens, whilst also preparing for postnatal immune defense by acquiring passive immunity from the mother. Since the perinatal period is regarded as the most important “window of opportunity” for imprinting metabolism and immunity, preterm birth may have long-term consequences for the development of immune-mediated diseases. Intriguingly, preterm neonates appear to develop bronchial asthma more frequently, but atopic dermatitis less frequently in comparison to term neonates. The longitudinal study of preterm neonates could offer important insights into the process of imprinting for immune-mediated diseases. On one hand, preterm birth may interrupt influences of the intrauterine environment on the fetus that increase or decrease the risk of later immune disease (e.g. maternal antibodies, placenta-derived factors), whereas on the other hand ,it may lead to the premature exposure to protective or harmful extra-uterine factors such as microbiota and nutritional antigen. Solving this puzzle may help unravel new preventive and therapeutic approaches for immune diseases.